Qualitative evaluation of kerf taper angle of conventionally drilled holes in glass fiber epoxy composite - Patil, Dipak S.; Bhoomkar, Manmohan M.; Sunheriya, Neeraj; Giri, Jayant; Kulkarni, Atul; Patil, Lalit N.; Toke, Lalit K.; Sathish, Thanikodi; Kanan, Mohammad (Frontiers in Mechanical Engineering, 2025)
This study analyses the impact of process parameters on Glass Fiber Reinforced Polymer (GFRP) components produced through conventional drilling on a CNC drilling machine (VMC). GFRP’s challenging machinability is due to its high strength-to-weight ratio, durability, and customizable mechanical properties. The study aims to minimize kerf angles in drilled holes, identifying optimal parameter combinations based on Signal-to-Noise ratios. The best combination of parameters that used to reduce the value of the kerf angle was considered at 2,800 RPM spindle speed and 1,200 mm/rev feed rate. The experimental work reveals that the spindle speed significantly affects the kerf angle, while the feed rate and spindle speed both influence the variation in the kerf angle and show the best results at the ideal values of the two parameters. The study details an analysis of the process parameters of drilled holes on kerf angle in multiple holes in the specimen, applying Taguchi’s design of experiments and analysis of variance. Comparison of findings was made with existing literature on determination of the importance of spindle speed and feed rate for the determination of kerf angle. The best results were obtained when all these parameters set to the ideal values, where the minimum angular kerf of 0.1145° was observed.